PENGEMBANGAN MEDIA PEMBELAJARAN ILMU PENGETAHUAN ALAM BERBASIS INTEGRASI SAINS DAN ISLAM PADA KELAS IV MI MAMBA’UL HUDA NGABAR PONOROGO - Iis Uun Fardiana (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2015)
Developing media through science and Islam intergration is a process of media development in the learning process assisted by using computer system and picture creation, animation, video, audio, and moving text, so that learning will not seem monotonous. In learning science that requires a lot of real knowledge can be realized with Macromedia Flash-based media integration of science and Islam. Because of that, teaching and learning process. Will be attractive and give positive influence on students’ natural science comprehension at MI Mamba’ul Huda Ngabar Ponorogo. Based on the research background, the objective of this research is to investigate those problems and to produce media based on science and Islam integration by using macromedia flash software and the output is in the form of CD (Compact Disc). This research used Research and Development methodology adapted from Dick and Carey methodology. To collect the data, the researcher applied interview, questionnaire, and observation. The result shows that, developing natural sciences learning media based on science and Islam integration are able to increase fourth grade students’ comprehension on natural science material at Madrasah Ibtidaiyah Mamba'ul Huda Ngabar Ponorogo. It can be seen from the mean of post test result 85.8, while in the pre-test the mean 76.8. Therefore, it can be concluded that the students get better score after using the media. Keywords: Development, Media-based integration of science and Islam, IPA.